2007
DOI: 10.1021/ma0700429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclopentadienyl and Anionic Donor Ligands on Monomer Reactivities in Copolymerization of Ethylene with 2-Methyl-1-pentene by Nonbridged Half-Titanocenes−Cocatalyst Systems

Abstract: Copolymerization of ethylene (E) with 2-methyl-1-pentene (2M1P) took place with rather efficient 2M1P incorporation by using the Cp*TiCl2(O-2,6- i Pr2C6H3) (1)−MAO catalyst system, whereas the 2M1P incorporations by the Cp2ZrCl2, [Me2Si(C5Me4)(N t Bu)]TiCl2, Cp‘TiCl2(NC t Bu2) [Cp‘ = Cp (3), Cp* (4)], and Cp*TiCl3−MAO catalyst systems were negligible under the same conditions. The effects of substituents in both the cyclopentadienyl and the aryloxide ligands tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 35 publications
3
65
1
Order By: Relevance
“…16 The MOD contents in the resultant copolymers were thus closely related to those in the ethylene/1 octene copolymerizations under the similar conditions.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…16 The MOD contents in the resultant copolymers were thus closely related to those in the ethylene/1 octene copolymerizations under the similar conditions.…”
mentioning
confidence: 68%
“…A known classic model of this approach is the introduction of unsaturation as exemplifi ed by using 5 ethylidene 2 norbornene, 1,4 hexadiene, and dicyclopentadiene (but showed ineffi cient incorporations in the copolymerization by ordinary catalysts). 11,30 Introduction of unsaturated olefi nic double bond into the side chain can be possible by adopting the copolymerizatioin of ethylene with 7 methyl 1,6 octadiene (MOD, scheme in Figure 1), 16,31 especially due to a difference in the reactivity of two olefi nic double bonds (terminal vs trisubstituted). However, their incorporations by the ordinary catalysts (metallocenes etc.)…”
Section: Synthesis Of Polyolefi Ns Containing Polar Functionalities Bmentioning
confidence: 99%
“…[41][42][43][44][45] In particular, 4-methylcyclohexene (4-MeCHE) and 1-methylcyclopentene (1-MeCPE) copolymers have been synthesized recently with nonbridged half-titanocenes containing anionic donor ligands of type, Cp'TiX2(Y) (Cp' = cyclopentadienyl group, Y = aryloxo, ketimide, phosphinimide etc.) [46].…”
Section: Microstructural Analysis Of Poly(ethylene-co-4-mechche) and mentioning
confidence: 99%
“…A known classic model of this approach is the introduction of unsaturation as exemplified by using 5-ethylidene-2-norbornene, 1,4-hexadiene, and dicyclopentadiene (but showed inefficient incorporations in the copolymerization by ordinary catalysts) [20] [31]. Introduction of unsaturatedolefinic double bond into the side chain can be possible by adopting thecopolymerizatioin of ethylene with 7-methyl-1,6-octadiene (MOD, Scheme 3) [29] [30] [32], especially due to a difference in the reactivity of two olefinic double bonds (terminal vs trisubstituted). However, their incorporations by the ordinary catalysts (metallocenes etc.)…”
Section: Synthesis Of Polyolefins Containing Polar Functionalities Bymentioning
confidence: 99%
“…However, their incorporations by the ordinary catalysts (metallocenes etc.) were inefficient, affording (co)polymers with low molecular weights as well as rather broad molecular weight distributions.We reported that copolymerizations of ethylene with 7-methyl-1,6-octadiene (MOD) by Cp*TiCl 2 (O-2,6-i Pr 2 C 6 H 3 ) (1)-MAO catalyst system afforded high molecular weight unsaturated poly(ethylene-co-MOD)s not only with high MOD contents, but also with exclusive incorporation of monoolefins (without incorporating trisubstituted olefin) [32]. The MOD contents in the resultant copolymers were thus closely related to those in the ethylene/1-octene copolymerizations under the similar conditions.…”
Section: Synthesis Of Polyolefins Containing Polar Functionalities Bymentioning
confidence: 99%